2016
DOI: 10.1055/s-0036-1596045
|View full text |Cite
|
Sign up to set email alerts
|

Isotretinoin Use in Thick-Skinned Rhinoplasty Patients

Abstract: One of the characteristics of mestizo patients can be the thick sebaceous skin associated with a poor osteocartilaginous underlying nasal structure. In spite of using a proper structural approach where grafts and sutures are used to define the nasal tip, frequently the results are suboptimal. Surgical techniques have been described to reduce the thickness of the skin-soft tissue envelope, but these frequently give unreliable results. The monitored use of isotretinoin given orally as a complement after performi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 37 publications
(68 reference statements)
0
40
0
Order By: Relevance
“…[6] All three of these patients underwent septorhinoplasty before starting oral isotretinoin treatment in the previous 2 years and all developed nasal tip deformities within 6 months of the initiation of isotretinoin treatment. Authors concluded that nasal tip deformity had developed due to isotretinoin's creation of imbalance between collagen production and degradation, as well as the accentuated “shrink and wrap” phenomenon associated with the abnormally thin nasal epidermis, and recommended postponing isotretinoin treatment for a minimum of 2 years following rhinoplasty;[6] however, Cobo and Vitery[7] reported that concomitant initiation of isotretinoin treatment with rhinoplasty helped to define the nasal tip and improved the surgical outcome in thick-skinned patients.…”
Section: Discussionmentioning
confidence: 99%
“…[6] All three of these patients underwent septorhinoplasty before starting oral isotretinoin treatment in the previous 2 years and all developed nasal tip deformities within 6 months of the initiation of isotretinoin treatment. Authors concluded that nasal tip deformity had developed due to isotretinoin's creation of imbalance between collagen production and degradation, as well as the accentuated “shrink and wrap” phenomenon associated with the abnormally thin nasal epidermis, and recommended postponing isotretinoin treatment for a minimum of 2 years following rhinoplasty;[6] however, Cobo and Vitery[7] reported that concomitant initiation of isotretinoin treatment with rhinoplasty helped to define the nasal tip and improved the surgical outcome in thick-skinned patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pre‐existing skin conditions like acne, rosacea, or eczematous disorders may exacerbate perioperatively. Consequently, in selected cases with difficult SSTE, the collaboration with a dermatologist may help optimize the SSTE preoperatively and avoid postoperative sequelae 1–5,9 …”
Section: Essentials In Rhinoplastymentioning
confidence: 99%
“…Surgeons usually classify the nasal skin into three main classes by inspection and palpation: thick, moderate, and thin skin. This classification is crucial for surgical planning 1–3,6 . So far, several objective methods such as computed tomography, magnetic resonance imaging, and ultrasound have been described to assess the thickness of the nasal SSTE.…”
Section: Preoperative Evaluation Of Sstementioning
confidence: 99%
See 2 more Smart Citations